Product improvement and storage stability study of sweet and spicy dilis (Stolephorus commersonii) - Payumo, Dolores Garcia; Gomez, Ma. Theresa L. (1993.)
Product improvement and storage stability of sweet and spicy dilis were studied. A standard formulation and procedure for sweet and spicy dilis were developed through a series of sensory evaluation trials. The maximum extent of reusability of the frying medium was determined using percent free fatty acid, smoke point temperature and mean scores for color, odor and clarity of used oil as indices in assessing the degree of degradation of cooking oil. The cost per 65-gram of the product was obtained from the bench scale production. The most suitable packaging material was chosen by determining the critical moisture content and the maximum allowable water vapor transmission rate of the product. The shelf life of the product was also estimated. Samples with 1:15 cayenne pepper to brown sugar ratio per 50 grams dried dilis was the most acceptable formulation. The best temperature of frying was found to be 180-185°C for smoke point temperature, the maximum reusability of coconut oil was determined to be 12 and 17 times, respectively. However, based on sensory evaluation trials the oil can be used for 6 times only. Thirty 65-gram packs of sweet and spicy dilis were obtained in the bench scale production which were costed at P7.54 pesos per pack comparable to the market price of existing products. Based on the critical moisture content of 3.18 % and a maximum allowable WVTR of 0.197 mg/100 sq. in. per day, polypropylene bag of thickness 0.002 inch was chosen as the packaging material. Shelf life was estimated at 30 days under conditions of 28°C and 81% RH. However, half value period under similar conditions of temperature and relative humidity was computed at 62 days.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fishery processing -- Philippines; Fishery products -- Storage; Dilis